Optimization of heat treatment process for high precision stamping dies - Ye, Weijiang. (2008)
Precision stamping is one of the fastest growing processes in the current metalworking industry. One of the key success factors in this field is to fulfill the precision requirement. However, there was rare information available on the influence of the heat treatment processes on the dimensional growth for both currently used and newly developed grades. This dissertation presents the extensive experimental works to evaluate the influence of austenitizing temperature, tempering condition, subzero treatment and post-tempering aging on the hardness, amount of the retained austenite, dimensional change during heat treatment, dimensional growth after heat treatment as well as un-notched impact toughness of ASSAB 88, ASSAB XW-42 and DAIDO DC 53 cold work tool steels.